2012
DOI: 10.1111/j.1559-1816.2012.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consideration of Future Consequences on Quality and Quantity Aspects of Job Performance1

Abstract: This study extended prior research on consideration of future consequences (CFC) by exploring its influence on quality and quantity aspects of job performance. CFC is an individual-differences variable reflecting the importance a person assigns to the immediate vs. future consequences of his or her actions. We hypothesized that individuals with a high future orientation would produce higher quality work, while low-CFC participants would produce greater quantities. Participants took part in a data-entry task wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
(38 reference statements)
2
32
0
3
Order By: Relevance
“…Other studies that have implemented the scale, confirmed acceptable reliability with Cronbach's a ranging from .80 to .86 (Toepoel, 2010). This scale has been used successfully in terms of alcohol consumption (Beenstock et al, 2010), discrimination of population samples (Ryack, 2012), aggression (Bushman et al, 2012), environmental impact (Joireman et al, 2004), exercise (Joireman et al, 2013;Van Beek et al, 2013), fast-food consumption (Dunn et al, 2011), health (Sirois, 2004;Kees, 2011), and job performance (Graso and Probst, 2012). Table 1 Example of statements Please complete the following statements thinking about your consumption of fast food/take-away food, and indicate your answer with an X in the relevant column:…”
Section: Research Design and Methodologymentioning
confidence: 78%
See 2 more Smart Citations
“…Other studies that have implemented the scale, confirmed acceptable reliability with Cronbach's a ranging from .80 to .86 (Toepoel, 2010). This scale has been used successfully in terms of alcohol consumption (Beenstock et al, 2010), discrimination of population samples (Ryack, 2012), aggression (Bushman et al, 2012), environmental impact (Joireman et al, 2004), exercise (Joireman et al, 2013;Van Beek et al, 2013), fast-food consumption (Dunn et al, 2011), health (Sirois, 2004;Kees, 2011), and job performance (Graso and Probst, 2012). Table 1 Example of statements Please complete the following statements thinking about your consumption of fast food/take-away food, and indicate your answer with an X in the relevant column:…”
Section: Research Design and Methodologymentioning
confidence: 78%
“…This study focused on young adults who are the primary household decision makers of the future-to provide empirical evidence of their concern about the consequences of their consumption of food-away-from-home, such as fast and take-away foods which has frequently been raised as a matter of concern by health professionals in recent years (Feeley et al, 2009;Van Zyl et al, 2010;Steyn et al, 2011;Shisana et al, 2013;Feeley and Norris, 2014;Sedibe et al, 2014;Ronquest-Ross et al, 2015). Until now, there have been no reports of the application of the CFC scale to consumers' food choice specifically (Graso and Probst, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has highlighted the importance of the future employment expectations by workers, clearly linked to educational level (Gallie et al, 2012). Workers with a high perception about the future of their jobs tend to get higher job quality (Graso and Probst, 2012). Thus, with the aim of contributing new evidence and reconciling the quantity and quality dimensions of employment policies in times of economic crisis (Green and Mostafa, 2012), this paper, which takes a multidimensional and micro-data empirical approach, analyses the determinants of job quality (Handel, 2005;Olsen et al, 2010;Esser and Olsen, 2012) in Spain for 2008 and 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has highlighted the importance of workers' future employment expectations, which are clearly linked to educational level (Gallie et al, 2012). Workers with a high perception of the future of their jobs tend to get higher job quality (Graso and Probst, 2012).…”
Section: Introductionmentioning
confidence: 99%